2004
DOI: 10.1089/089771504322778604
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Abuse and Traumatic Brain Injury: Quantitative Magnetic Resonance Imaging and Neuropsychological Outcome

Abstract: Prior or concurrent alcohol use at the time of traumatic brain injury (TBI) was examined in terms of post-injury atrophic changes measured by quantitative analysis of magnetic resonance imaging (MRI) and neuropsychological outcome. Two groups of TBI subjects were examined: those with a clinically significant blood alcohol level (BAL) present at the time of injury (TBI + BAL) and those without a significant BAL (TBI-only). To explore the potential impact of both acute and chronic alcohol use, subjects in both g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 76 publications
3
47
1
Order By: Relevance
“…As well, injuries in more, rather than less, body regions are generally more severe. Thus our findings are consistent with other recent research indicating that alcohol involvement increases with injury severity (Levy et al, 2004;Wilde et al, 2004). However, head injuries and multiple injury locations are correlated with violence and crashes, which in absolute numbers represent more than half of the sample in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As well, injuries in more, rather than less, body regions are generally more severe. Thus our findings are consistent with other recent research indicating that alcohol involvement increases with injury severity (Levy et al, 2004;Wilde et al, 2004). However, head injuries and multiple injury locations are correlated with violence and crashes, which in absolute numbers represent more than half of the sample in this study.…”
Section: Discussionsupporting
confidence: 93%
“…No significant relationships were found. However, other studies indicate that alcohol involvement increases with injury severity (Levy et al, 2004;Wilde et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Volumetric analysis allows for the detection or quantification of white and gray matter volumes, either globally or for specific regions, as well as cerebrospinal fluid and total intracranial volume, generally using threedimensional (3-D) volumetric high resolution T1-weighted imaging or combinations of complementary MR sequences. Volumetric analysis using specific regions has demonstrated significant decreases in volume in both adult (Tomaiuolo et al, 2004;Warner et al, 2010a;Wilde et al, 2004Wilde et al, , 2006a and pediatric (Beauchamp et al, 2010;Fearing et al, 2008;Spanos et al, 2007;Wilde et al, 2005Wilde et al, , 2006bWilde et al, , 2007Wu et al, 2010a) subjects with TBI in the chronic post-injury interval. Additionally, voxel-based, whole-surface based, and tensorbased analyses have also demonstrated significant global reductions in cortical thickness (Merkley et al, 2008) and cortical gray matter volume Ding et al, 2008;Gale et al, 2005;Warner et al, 2010a,b) as well as white matter volume (Ding et al, 2008;Sidaros et al, 2009;Vannorsdall et al, 2010).…”
Section: Mrimentioning
confidence: 99%
“…A history of chronic alcohol abuse prior to TBI is associated with a higher prevalence of mortality [13], poorer outcome [13] and is known to influence GCS, length of posttraumatic amnesia (PTA), duration of acute rehabilitation and hospital stay [17]. Moreover, several studies have found an additive effect of substance abuse on neuropsychological outcome in TBI [7,[18][19][20][21][22]. A recent study by Vickery et al [23] investigated the relationship between intoxication at time of injury, pre-injury history of problem drinking and early functional status in patients with TBI admitted to an inpatient rehabilitation setting.…”
Section: Introductionmentioning
confidence: 99%